(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2023)
The reforms carried out in the country are based on programs and strategies developed on the basis of national values, relying on the effective experiences of developed countries. Including in the reform of the educational system, a national system was developed, in which the experiences of different states were studied. In addition to public organizations and agencies, it also focuses on the issues of establishing activities in cooperation with public organizations and other civil institutions.